Analysis of Macro Element Composition in Organic Manure Derived from Cow Dung, Sawdust, and Charcoal for Enhanced Productivity of Arable Crops and Vegetables - AKINFIRESOYE, Waleola Ayo; OGIDAN, John Akintomide; OLUMAKINWA, Christianah Dolapo (ABUAD Journal of Engineering and Applied Sciences, 2024)
The increase in the cost of inorganic fertiliser and the danger it poses to the health of consumers when used to grow crops motivated the production of pelletised organic manure (OM) from fresh cowdung (CD), sawdust (SD), and charcoal (CH) at the demonstration farm of the Agricultural Technology Department, Federal Polytechnic, Ile Oluji. CD, SD, and CH were mixed based on weight ratios of 2:1:1 and 1:1:1, respectively, and allowed to decompose anaerobically for 21 days. OM produced was subjected to macro element presence and was discovered to be rich in nitrogen (N), phosphorus (P), and potassium (K), which were the major elements needed for growing arable crops and vegetables. The percentage of the NPK slightly increased as the weight of the CD increased. NPK contents were 1.21%, 0.83%, and 1.12%, respectively, for the CD, SD, and CH ratios 2:1:1, while it was 0.81%, 0.6%, and 0.73% for ratios 1:1:1, respectively. The temperatures of the OM were 38 °C and 36 °C for the two ratios, respectively, and the pH was 8.8 and 8.4, respectively, at the end of the 21 days of decomposition. Based on this analysis, the OM produced is recommended for growing arable crops and vegetables. It will equally give the youths employment opportunities and assist the nation in converting waste into wealth.